2020
DOI: 10.1186/s12936-020-3117-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the persistence of malaria in Rwanda

Abstract: Background: Malaria has a considerable impact on the health of the populations of developing countries; indeed, the entire population of Rwanda is at risk of contracting the disease. Although various interventions to control malaria have been implemented in Rwanda, the incidence of malaria has increased since 2012. There is an interest in understanding factors driving its persistence in Rwanda. This study aims at evaluating the effect of socioeconomic and environmental factors, seasonality and the use of insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 18 publications
3
40
0
1
Order By: Relevance
“…The results from this study also revealed that the malaria prevalence was higher among children from the Eastern Province compared to children from the other provinces. This finding is consistent with the findings from other studies [ 2 , 39 ]. This may be due to the Eastern Province’s generally low altitude, compared to other Rwandan provinces and its many open water sources, which serve as reservoirs for mosquito breeding sites and thereby increase the risk of malaria infection [ 37 , 38 , 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…The results from this study also revealed that the malaria prevalence was higher among children from the Eastern Province compared to children from the other provinces. This finding is consistent with the findings from other studies [ 2 , 39 ]. This may be due to the Eastern Province’s generally low altitude, compared to other Rwandan provinces and its many open water sources, which serve as reservoirs for mosquito breeding sites and thereby increase the risk of malaria infection [ 37 , 38 , 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…Malaria, which is endemic in both tropics and subtropics, remained one of the preventable and curable diseases that has continued to threaten human health and survival especially among young children [ 1 ]. It is one of the world’s most deadliest diseases that causes significant public health challenge.…”
Section: Introductionmentioning
confidence: 99%
“…P. falciparum and other malaria-causing species are mainly present in Africa and parts of Rwanda [24], the study site. The 19 analyzed clinical cases represented examples of sick children, pregnant women and acute or complicated forms of a parasitic disease that causes thousands of deaths, which occur worldwide every year.…”
Section: Discussionmentioning
confidence: 99%